Medication non-adherence among outpatients with myocardial infarction: A hospital-based study - Anan S. Jarab; Razan Z. Mansour; Suhaib Muflih; Walid Al-Qerem; Shrouq R. Abu Heshmeh; Tareq Mukattash; Yazid N. Al Hamarneh; Maher Khdour (Elsevier, 2024)
Background: Despite the availability of effective medications for the treatment of myocardial infarction (MI), treatment outcomes are suboptimal due to medication non-adherence. The aim of this study was to assess medication adherence and its associated factors among patients with MI. Methods: This cross-sectional study was conducted on outpatients with MI in the cardiology clinic at a major hospital in Jordan. Medication adherence was assessed using the validated Arabic version of the 4-item Medication Adherence Scale. Ordinal regression was conducted to identify the variables associated with medication non-adherence. Results: A total of 333 patients participated in the study. The median age was 58 years (57-60). Medication non-adherence was expressed by 54.6 % of the participants. Having less than college/university education (Coefficient = −0.625, 95%Cl (−1.191 to −0.06), P = 0.03) and increased medication-related concerns (Coefficient = −0.065, 95 % Cl (−0.126 to −0.003), P = 0.04) were associated with decreased medication adherence. Other factors, including having no family history of cardiovascular disease (CVD) (Coefficient = 0.757, 95%Cl (0.218-1.295), P = 0.006) and increased medication necessity (Coefficient = 0.186, 95%Cl (0.133-0.239), P < 0.001) were associated with high medication adherence. Conclusion: The current study demonstrated a high rate of medication non-adherence in MI patients, necessitating the need to develop tailored pharmaceutical care interventions that address patients' medication-related beliefs, focusing on their perceptions of medication necessity and concerns, particularly in patients with low education level and those with a positive family history of CVD.